Human amnion epithelial cells induce M2 macrophage polarisation partially via M-CSF secretion but independently of extracellular vesicles in vitro - Zeijlon, Louise; Budhwar, Snehil; Lindau, Robert; Bencina, Stefan; Kaipe, Helen; Jenmalm, Maria C.; Gramignoli, Roberto; Raffetseder, Johanna (Frontiers in Immunology, 2026)
Pregnancy requires major immunomodulatory changes, both systemically and locally, as the maternal immune system needs to be modulated to tolerate the semi-allogeneic foetus. Decidual macrophages and stromal cells, but also foetal tissues are involved in this immune tolerance, for example by inducing M2 macrophages and regulatory T cells. However, it is so far unknown whether foetal membrane cells such as amnion epithelial cells (AECs) can influence human macrophage polarisation. In this study, a human in vitro macrophage assay was employed to demonstrate that conditioned medium (CM) from AECs derived from term placentas induces M2 macrophage polarisation, and to compare AEC culture conditions aiming for efficient M2 polarisation. Macrophage colony-stimulating factor (M-CSF), a well-known M2-inducing cytokine, was found to be secreted by AECs, and M-CSF was partly responsible for the observed M2-polarising effect of AECs. In addition, the M2-polarising effect remained after removal of extracellular vesicles (EVs) from AEC-CM, suggesting the involvement of soluble but not of EV-associated mediators. Taken together, this study shows that AECs may contribute to the induction of the vital immunotolerant environment at the foetal-maternal interface. Based on their immunomodulatory effects observed here and in in vivo studies, AECs could be harnessed as cytotherapeutics for inflammatory disorders.